Transition from nonuse to use of alcohol or binge drinking among adolescents: Secondary analysis of a randomized controlled trial. (March 2020) - Conegundes, Lara; Valente, Juliana Y.; Cogo-Moreira, Hugo; Martins, Camila Bertini; Andreoni, Solange; Sanchez, Zila M.
Highlights: Parents' alcohol consumption and the absence of the father at home seem to be predictors of early alcohol use and binge drinking initiation. Students' violent behavior at baseline seems to predict alcohol use initiation. School drug prevention programs should tackle violent behavior at an early age and also address parents' alcohol consumption practices. Abstract: Objective: The objective of this study was to evaluate the predictors of the transition from nonuse of alcohol to the first use of alcohol and the first episode of binge drinking. Methods: Data were drawn from a randomized controlled trial conducted with seventh- and eighth-grade students from 72 public schools over a 21-month period in six cities in Brazil. A total of 3298 students who reported that they had never consumed alcoholic beverages and had never engaged in binge drinking at baseline were included in this study. The two binary outcomes were tested concomitantly via structural equation modeling. Maximum likelihood estimates for logistic regression models were performed to evaluate how baseline data regarding risk factors, such as sociodemographic characteristics (socioeconomic status, gender, and age), school experiences (violence and perception of academic performance), and social variables (family and friends), affected the initiation of alcohol use and binge drinking at 9- and 21-month follow-up assessments. Results: Older age, the perpetration of violent behaviors at baseline and the absence of the father living with the adolescent were predictors of both alcohol use initiation and binge drinking initiation. The #Tamojunto program showed iatrogenic effect for first alcohol use. Conclusions: The results indicate the need to develop and implement effective alcohol prevention programs that consider the main characteristics in the prediction model for alcohol consumption and binge drinking, including early intervention for aggressive behaviors at school and parental alcohol use.